PENGEMBANGAN ABON NANGKA IKAN BERBASIS TEKNOLOGI PENGAWETAN BAHAN LOKAL DAN PENINGKATAN GIZI PADA KELOMPOK PEREMPUAN PEMERHATI LINGKUNGAN - Sari, Selly Ratna; Silsia, Devi; koto, hidayat; Wulandari, Sri (Jurnal Abdi Insani, 2025)
The Prosperous and Sumber Jaya Women's Environmental Observer Group (KPPL) is located in Rejang Lebong District, Bengkulu Province. This group has been established as a cooperative and produces various processed foods. The main raw materials focused on by the group are jackfruit and avocado. The aim of this service activity is to enhance the knowledge and skills of the women's environmental observer group (KPPL) in developing processed jackfruit into shredded, preservation-based products to increase its nutritional value. The service method includes surveys, socialization through material presentations, hands-on practice in producing processed jackfruit combined with fish, the preservation process, and the design of activity evaluations using pre-test and post-test results. The level of understanding of participants about jackfruit products whether they need to be preserved, several types of food preservatives and jackfruit can be used as shredded jackfruit when pretested is high, namely above 70% (86.96%, 95.65% and 91.30%). The combination of jackfruit and fish products, as well as agricultural and fishery materials can be used for food preservatives at the time of the pre-test needs to be highligh (highlighted) with the percentage of participants who know that it is still below 70% (65.22 and 26.09). Overall, participants experienced an increase in knowledge before the activity (pre-test results) and after the activity (post-test results).